Poor effectiveness of antenatal detection of fetal growth restriction and consequences for obstetric management and neonatal outcomes: a French national study. (27th October 2014) - Monier, I; Blondel, B; Ego, A; Kaminiski, M; Goffinet, F; Zeitlin, J
<x xml:space="preserve">Abstract</x> Objective To assess the proportion of small for gestational age (SGA) and normal birthweight infants suspected of fetal growth restriction (FGR) during pregnancy, and to investigate obstetric and neonatal outcomes by suspicion of FGR and SGA status at birth. Design Population‐based study. Setting All French maternity units in 2010. Population Representative sample of singleton births (n = 14 100). Methods We compared SGA infants with a birthweight of less than the 10th percentile suspected of FGR, defined as mention of FGR in medical charts (true positives), non‐SGA infants suspected of FGR (false positives), SGA infants without suspicion of FGR (false negatives) and non‐SGA infants without suspicion of FGR (true negatives). Multivariable analyses were adjusted for maternal and neonatal characteristics hypothesised to affect closer surveillance for FGR and our outcomes. Main outcome measures Obstetric management (caesarean, provider‐initiated preterm and early term delivery) and neonatal outcomes (late fetal death, preterm birth, Apgar score, resuscitation at birth). Results 21.7% of SGA infants (n = 265) and 2.1% of non‐SGA infants (n = 271) were suspected of FGR during pregnancy. Compared with true negatives, provider‐initiated preterm deliveries were higher for true and false positives (adjusted risk ratio [aRR], 6.1 [95% CI, 3.8–9.8] and 4.6 [95% CI, 3.2–6.7]), but not for false negatives (aRR, 1.1 [95% CI, 0.6–1.9]). Neonatal outcomes were not better for SGA infants if FGR was suspected. Conclusion Antenatal suspicion of FGR among SGA infants was low and one‐half of infants suspected of FGR were not SGA. The increased risk of provider‐initiated delivery observed in non‐SGA infants suspected of FGR raises concerns about the iatrogenic consequences of screening.